Does NGO Aid Go to the Poor? : Empirical Evidence from Europe - Nancy, Gilles (IMF Working Papers; Working Paper ;, 2006)
This paper studies the aid allocation of European nongovernmental organizations (NGOs). Once population is controlled for, poverty consistently appears as the main worldwide determinant of NGO aid allocation. NGOs do not respond to strategic considerations. Their funding source does not seem to exert a great influence on their aid allocation decision. We also find differences across regions. Militarization and the political nature of the regime of the recipient country affect aid allocation in the Middle East. Life expectancy influences aid allocation in countries in the Western Hemisphere and the Middle East.